Gestão financeira e de fluxo de caixa em escolas particulares de Educação Básica - Jesus, Ricardo Luiz de (2022)
The objective of the study is to contribute to improving the financial management and cash flow of private elementary schools. Therefore, the study was based on private schools located in the metropolitan area of São Paulo with the objective of deepening the understanding the risk of operation of schools (K12) in the private education network, enabling the use of service contracts as collateral in the anticipation of receivables to optimize the cash flow management processes during the school year. For this to be possible, it is necessary to reduce the asymmetry of information between the educational and financial sectors and the consequent adverse selection, which is considered as a risk factor in the composition of interest rates and/or discounts of anticipation of receivables in financial operations that are currently contracted by schools with commercial banks. This approach can provide an adequate operational and financial risk assessment, and also create a methodology to manage the future revenue streams of these institutions so that they can be anticipated and thus, meet the need for working capital when cash flow mismatches occur, in addition to natural events that are already known as late payments on monthly dues, payment of vacations and their additional payments concentrated on school vacations, keeping payments of unavoidable commitments up to date so that financial commitments favor the school operation, which leads us to the fundamental question: Can an anticipation of receivables model reduce the cost of raising working capital? This proposal suggests a change in financial management capable of organizing contracts and receivables with a view to reducing information asymmetry and allowing the negotiation of this flow of receipts with banks, investment funds and credit fintech’s in better conditions for schools. It considers a new approach to the use of the future flow of receivables in financial negotiations: as a way of adjusting mismatches between cash inflows and outflows with the flows of future receipts, which is not the current practice. We will assess the basic education sector and its financial management: the risk of the basic education business and the history of opening and closing schools in the last 20 years, operational and financial processes, education's service contracts and receivables generated by these, in addition to pointing out and recommending the use of common operations in the financial market such as the anticipation of receivables that are uncommonly used by schools in financial management. It is hoped that this work will contribute to the creation of a set of procedures that can improve the financial results of private schools.